PATHOLOGICAL MIGRATION OF TEETH THROUGH PERIODONTAL DISEASE AND THE VALUE OF ORTHODONTIC THERAPY IN INCREASING THE QUALITY OF LIFE. REVIEW. - Maria-Alexandra Martu; Ionut Luchian; Ioana-Andreea Sioustis; Liliana Pasarin; Irina-Georgeta Sufaru; George-Alexandru Maftei; Andra Gamen; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2021)
Orthodontic treatment can successfully align pathologically migrated teeth leading to improved periodontal stability in patients with periodontal disease. Periodontal-orthodontic approaches have gained increasing attention in recent years. A considerable number of adult patients with periodontal disease are interested in orthodontics in order to improve the alignment of their teeth. However, the severity of periodontal disease and dental incongruence or demographic factors cannot be indicative of these. Elderly patients were significantly more frequently interested in orthodontic treatment. Most study participants were not provided with information on orthodontic treatment options for adults. Very importantly, this group of patients must be aware of the need to stabilize their periodontal condition, to maintain high standards of oral hygiene, before any orthodontic intervention. Therefore, practitioners need to be aware of the patient's need, deliver patient-centered and provide them with relevant information and, if necessary, plan interdisciplinary treatment.